Pinitol suppresses TNF-α-induced chondrocyte senescence. (June 2020) - Lou, Chunbiao; Deng, Aiwei; Zheng, Huiming; Sun, Guiying; Zhao, Huaqin; Li, Aixia; Liu, Qian; Li, Yang; Lv, Zhiqiang
Abstract: Osteoarthritis (OA) is a highly prevalent joint disorder that is tightly correlated with age. As the body ages, cell replication and function decline until homeostasis can no longer be maintained. This process involves cellular senescence as well as replicative senescence. Telomere length, cell cycle arrest, expression of p16 and p53, and the release of senescence-associated β-galactosidase (SA-β-Gal) are all markers of cell senescence. In OA joints, chondrocytes undergo cellular senescence prematurely, thereby ceasing to synthesize and maintain cartilage tissue. Upregulation of proinflammatory cytokines, such as tumor necrosis factor-α (TNF-α), and oxidative stress induced by overproduction of reactive oxygen species (ROS) are key events in the pathogenesis of OA. In the present study, we investigated the effects of pinitol, a naturally occurring compound, on the effects of TNF-α on chondrocyte senescence and cell cycle arrest. We found that pinitol has a favorable safety profile in terms of cell viability. Pinitol significantly inhibited cellular senescence and cell cycle arrest in the G0/G1 phase induced by TNF-α. We also found that pinitol could inhibit TNF-α-induced increased telomerase activity and expression of p16 and p53. Importantly, we found that the effects of pinitol may be mediated through rescue of Nrf2 signaling, which is recognized as a key protective factor in OA. This finding was verified through a Nrf2 silencing experiment using Nrf2 siRNA. Together, our findings reveal the potential of pinitol as a safe therapeutic option for the prevention of OA-associated chondrocyte senescence and oxidative stress.